Moderating role of quality governance between green marketing strategies and organizational performance in Malaysia - Hasan, Zuhairah (2019)
The main purpose of this study is to investigate the impact of green marketing strategies on organizational performance. This research empirically examines the green marketing strategies practices by the ISO 14001 Environmental Management System certified firms in Malaysia. This research addresses the issue on green marketing and attempt to provide an insight into the green marketing strategies practices by the ISO 14001 Environmental Management System certified firms in Malaysia. In ensuring the success of the green initiatives for better performance, this study will include the role of quality governance as a moderating factor between the green marketing strategies and organizational performance. Moreover, there has been limited literature on green marketing strategies which consists of green product, green price, green promotion, green distribution, strategic competency (top management and mission and vision) and marketing resources (physical resources and financial resources) as a success factor thus far. The relevant theories to show how they support the expected relationships between green marketing strategies, quality governance and organizational performance are Resource-Based View theory and Stakeholder theory. This study is using ISO 14001 EMS certified firms as survey sample and questionnaires as the main research instrument. A total of 150 responses were collected using simple random sampling technique. This study will employ partial least square-structural equation modelling (PLS-SEM) as the main statistical technique. The analysis assessment of the measurement model was performed to examine the correlation between construct and items. Next, the study assesses the structural model, which resulted that five out of eight hypotheses were supported. The results of testing the hypotheses that predicted; green product, green pricing, top management, mission and vision and financial resources significantly positively affects organizational performance. However, predictors such as green promotion, green distribution and physical resources is found to be not significantly related. The research also led to the importance of governance on the green marketing strategies implementation. The analysis on the moderating effect of quality governance on the relationship between the independent variables (green marketing strategies) and organizational performance indicated that, quality governance does not moderate the relationship between (green product, green pricing, green promotion, vision and mission, top management and physical resources) and organizational performance. Results show that quality governance weaken the relationship between (green distribution and financial resources) and organizational performance. The study is expected to bring in new findings as the past literature does not provide any sufficient evidence for the proposed model. Management implications to re-orient their marketing strategies are discussed. Recommendations and implications for further research are mentioned detail.